2014
DOI: 10.1007/s12015-013-9494-8
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma (PRP) Promotes Fetal Mesenchymal Stem/Stromal Cell Migration and Wound Healing Process

Abstract: Numerous studies have shown the presence of high levels of growth factors during the process of healing. Growth factors act by binding to the cell surface receptors and contribute to the subsequent activation of signal transduction mechanisms. Wound healing requires a complex of biological and molecular events that includes attraction and proliferation of different type of cells to the wound site, differentiation and angiogenesis. More specifically, migration of various cell types, such as endothelial cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 57 publications
3
78
0
3
Order By: Relevance
“…However, fetal platelets may also produce factors that actively promote tissue regeneration, in part, through the recruitment of mesenchymal stem cells (MSCs). 20 Further elucidation of the chemokine profile from fetal tissues during homeostatic conditions and from the midgestation scarless wound healing, late-gestation transitional wound healing, and postnatal stages is required to understand the factors leading to reduced inflammatory infiltrates in fetal wounds.…”
Section: The Hemostasis Stage Of Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fetal platelets may also produce factors that actively promote tissue regeneration, in part, through the recruitment of mesenchymal stem cells (MSCs). 20 Further elucidation of the chemokine profile from fetal tissues during homeostatic conditions and from the midgestation scarless wound healing, late-gestation transitional wound healing, and postnatal stages is required to understand the factors leading to reduced inflammatory infiltrates in fetal wounds.…”
Section: The Hemostasis Stage Of Wound Healingmentioning
confidence: 99%
“…79 Furthermore, Roubelakis et al 20 recently reported that platelet-rich plasma promotes regenerative wound healing through recruitment of MSCs. Together these data suggest that there may be a role for circulating stem and progenitor cells in the fetal response that may similarly be, in part, regulated by chemokines.…”
Section: Chemokines In Fetal and Adult Wound Healingmentioning
confidence: 99%
“…Shin et al demonstrated that incubating dermal fibroblasts in 20 % platelet-rich clot (P-PRP) releasate for 48 h markedly up-regulated the expression of both MMP-1 and type I collagen in dermal fibroblasts [14]. Roubelakis et al showed that the presence of P-PRP in a fetal mesenchymal stem cell medium resulted in a significant induction of the migration ability and the proliferation rate of mesenchymal stem cells and dermal fibroblasts [15] ( Table 2).…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Tajima et al [11] Increased growth factor secretion by adiposederived stem cells Roubelakis et al [15] Promoted migration and proliferation of mesenchymal stem cells and dermal fibroblasts…”
Section: Animal Studiesmentioning
confidence: 99%
“…The key regenerative medicine products into the clinical usage being evolved includes Stem cells, mesenchymal stem cells and platelet rich plasma (PRP) [7,8] .The PRP was initially promoted by M. Ferrari in 1987 [9] as an autologous transfusion component after an open heart operation to avoid homologous blood product transfusion, there are now over 5200 entries in the NCBI for PRP across different disorders including wound healing, cosmetic, bone healing, osteoarthritis, hair transplantation and musculoskeletal tendonitis [10,11]. The platelets are rich in proteins, contain growth factors and cytokines.…”
Section: Introductionmentioning
confidence: 99%